Separation of Spherical Nanosilica from Agricultural Wastes in Vietnam via Ultrasonic-Assisted Precipitation and Application for Effective Removal of Methylene Blue from Aqueous Solution - Nguyen Duc Vu Quyen; Tran Ngoc Tuyen; Dinh Quang Khieu; Ho Van Minh Hai; Dang Xuan Tin; Bui Thi Hoang Diem; Le Van Thanh Son; Nguyen Thi Kieu Diem; Le Thi Nguyet; Bui Thi Thuy; Ho Thi Thuy Dung (Journal of Nanotechnology)
Agricultural wastes including bagasse and rice husk ashes are employed for synthesizing spherical nanosilica materials via the ultrasonic-assisted precipitation process in the present study. The comparison between them and nanosilica prepared from pure sodium silicate is also carried out. The role of the NH4OH : ethanol volume ratio is demonstrated. The obtained nanosilica is characterized by modern methods including X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDS), infrared spectroscopy (IR), scanning electron microscopy (SEM), and nitrogen adsorption/desorption isotherms (BET). The nanosilica material is employed as an effective adsorbent for the removal of methylene blue (MB) from an aqueous solution. The suitable pH and adsorbent dosage are determined at 8 and 0.375 g·L−1. The adsorption isotherm study is surveyed based on Langmuir and Freundlich isotherm models. Pseudo-second-order kinetic model and Weber–Morris intraparticle diffusion model well describe the chemical nature of the adsorption. The thermodynamic parameters of the reaction are determined based on the Van’t Hoff equation.